The current state of transcatheter aortic valve replacement explant: an updated systematic review - Sá, Michel Pompeu; Ashwat, Eishan; Jacquemyn, Xander; Ahmad, Danial; Brown, James A.; Serna-Gallegos, Derek; Osho, Asishana; Bloom, Jordan P.; Sultan, Ibrahim (Annals of Cardiothoracic Surgery, 2024)
Background: Despite ever-growing adoption of transcatheter aortic valve replacement (TAVR) in younger healthier patients, a limited number of studies have described post-TAVR valve reinterventions such as surgical explantation known as “TAVR explant”. Methods: We performed a systematic review to characterize the current state of TAVR explant in patients with a failing transcatheter heart valve (THV) using data published by April 30, 2024 in compliance with the PRISMA and MOOSE reporting guidelines. The protocol was registered in PROSPERO (CRD42024529188). Results: Twenty-eight studies met the eligibility criteria. Almost all studies were non-randomized, observational, and retrospective. The incidence of TAVR explant ranged from 0.2% to 2.8% in patients with a mean age of 67.3–79.0 years, and women representing 25.0–47.1% of cases. The mean time between TAVR implant and explant was 17.0–674.9 days, with most studies reporting a mean time 5%), the STS-PROM score at the time of the TAVR explant ranged between 3.9% and 9.9% (with 17 studies with score >5%). Isolated surgical aortic valve replacement (SAVR) happened in 16.2–100% of cases, aortic root replacement was required in 2.6–41.2%, ascending aortic replacement was performed in 3.2–33.3% of cases. Mitral valve repair/replacement was necessary in 11.8–43.5% and tricuspid valve/repair replacement was done in 2.8–25.0%. Stroke rates were between 0.0% and 20.0% with most studies with rates above 4.0%. The 30-day death rate ranged from 4.8% to 50.0% with most studies with mortality rates higher than 10%. Observed-to-expected mortality ratio was higher than 1.0 in almost all the studies that reported this variable. Conclusions: TAVR explant remains a rare event, but its clinical impact is non-negligible. Lifetime management strategies should be adopted in younger lower-risk patients when choosing THVs for the index TAVR.